IMPLEMENTASI METODE STORYTELLING DALAM MENANAMKAN NILAI-NILAI ISLAM PADA SISWA DI TADIKA SURIA PERDANA - Ayu Syahputri, Indah; Hasrian Rudi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the storytelling method in instilling Islamic values in students at Tadika Suria Perdana. The storytelling method was chosen because storytelling activities are considered capable of attracting children's attention and helping them understand the moral messages conveyed. This study used a qualitative approach with a case study type. Data were obtained through observation, interviews, and documentation conducted directly at the research location. The data analysis technique was carried out through the stages of data reduction, data display, and conclusion drawing, while the validity of the data was tested through technique triangulation and source triangulation. The results of the study show that storytelling activities are carried out by delivering Islamic stories, such as stories of the prophets and exemplary figures in Islam. Through these stories, teachers instill Islamic values in children such as honesty, responsibility, patience, obedience, and religious attitudes. In addition, storytelling activities also help improve children's learning interest, listening skills, and imagination. The learning process delivered through stories makes it easier for students to understand moral messages and apply them in their daily lives. Therefore, the storytelling method can be one of the effective ways for teachers to instill Islamic values in early childhood.